The Relationship of Age and Gravida Status with The Incident of Anemia in Pregnant Women in Tanjung Karang Community Health Center - Susilia Idyawati; Baiq Ricca Afrida; Ni Putu Aryani; Sri Hawari Jannati (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2024)
The incidence of anemia in pregnant women in Indonesia is still relatively high, namely 48.9%. This shows that anemia in Indonesia is quite high and is approaching a serious public health problem with an anemia prevalence limit of more than 40%. The aim of this study was to identify risk factors for anemia in pregnant women. This research method is cross-sectional; the research subjects are pregnant women at the Tanjung Karang Community Health Center from January to July 2023, with a sample size of 170 pregnant women. Historical data analysis uses bivariate analysis with the Chi square method. Results of data analysis show that the highest age is 20-35 years, 66 years, and the lowest age is >35 years, 5%, depending on the fetus's condition. The highest was in women with multiple pregnancies, 44 years, and the lowest was with multiple pregnancies, 13 years. The results of data processing show that the maximum maternal age is 112 pregnant women, or 66% with reproductive age, namely 20–35 years of age. In this age group, 50% of pregnant women experience anemia, and 16% do not experience anemia. The statistical test results obtained a value of p=0.298. (P > 0.05), this shows that there is no relationship between maternal age and anemia in pregnant women. There were 73 primigravidas, or 38%, and 64 of the 170 pregnant women experienced anemia, while the remaining 9 people, or 3%, did not experience anemia. The statistical test results obtained p = 0.003, which means there is a relationship between gravida status and the incidence of anemia. The results of this study showed that there was no relationship between age and the incidence of anemia, and there was a relationship between gravida status and the incidence of anemia.